PENGARUH MODEL STRUKTURAL ANALITIK SINTETIK (SAS) TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I DIMASA PERUBAHAN KURIKULUM MERDEKA DI SDN 190 PEKANBARU: Asih Wulan Dari - Asih Wulan Dari; Zaka Hadikusuma Ramadan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe the influence of the Structural Analytic Synthetic (SAS) model on the early reading skills of first-grade students during the curriculum change towards the Merdeka Curriculum at SDN 190 Pekanbaru. This research employed a quantitative method with an experimental approach using a pre-experimental design, specifically the one-group pretest-posttest design. The research subjects were all first-grade students of SDN 190 Pekanbaru, totaling 55 students divided into two classes. Data analysis was carried out through descriptive statistical analysis and inferential statistical testing, including instrument validity and reliability tests, as well as pretest and posttest score analysis. The results showed that the use of the Structural Analytic Synthetic (SAS) model had a significant influence on the early reading skills of the first-grade students at SDN 190 Pekanbaru. Based on the instrument validity test results, the learning module achieved a validity rate of 97%, and the test items achieved 83%, both categorized as highly valid. The reliability test using Cronbach’s Alpha produced a value of 0.767, indicating that the test items were reliable. The normality test results showed that the data were normally distributed with a significance value of 0.200 for the experimental class pre-test and 0.087 for the post-test, while the control class pre-test scored 0.052 and the post-test scored 0.065, all exceeding the 0.05 threshold. The homogeneity test resulted in a significance value of 0.069, indicating that the data had homogeneous variances. After data analysis, the experimental class post-test scores were found to be higher than those of the control class, proving that the SAS model was effective in improving students' early reading skills.